Application Solar Energy for Charging Battery Mobile Phone - Elmahdi, Mohamed Abdulhadi; Suparman, Sudjito; Pramono, Sholeh Hadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Photovoltaic energy is the conversion of sunlight into electricity. A photovoltaic cell, commonly called a solar cell or PV, is the technology used to convert solar energy directly into electrical power. A battery charger is a device used to put energy into a secondary cell or recharge able battery by forcing an electric current through it. Digital devices, especially mobile phones, need electricity that can be obtained from local electricity station converted into direct current using proprietary charger. Yet, the users can not always find the local electricity station such as in travelling or in condition where electricity becomes unavailable at the moment. On the other side, the use of local electricity to power mobile phones increases the fossil fuel consumption since the main source of energy for our current local. The solar energy is the ideal solution to the problems of energy and the environment and provides environmental safety factor as the solar energy is clean, renewable energy does not pollute the air and leave no waste. The charge controller is divided into two circuits: overcharge controller and discharge controller. Overcharge controller limits the maximum voltage when recharging process is being held. The circuit implemented is an operational amplifier that works as comparator, of which output controls the transistor that will stop or allow the charging current passed to the battery, the result is able to meet the design characteristics for the controller. These results are very useful for charging battery form sun light and it’s more economical and environmentally friendly and the advantage of the system compared to charger mobile phone ac to dc. And this solution for the electrification of remote areas.Keywords: controller, solar panel, battery .